2021
DOI: 10.1038/s41467-021-23235-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning predicts cardiovascular disease risks from lung cancer screening low dose computed tomography

Abstract: Cancer patients have a higher risk of cardiovascular disease (CVD) mortality than the general population. Low dose computed tomography (LDCT) for lung cancer screening offers an opportunity for simultaneous CVD risk estimation in at-risk patients. Our deep learning CVD risk prediction model, trained with 30,286 LDCTs from the National Lung Cancer Screening Trial, achieves an area under the curve (AUC) of 0.871 on a separate test set of 2,085 subjects and identifies patients with high CVD mortality risks (AUC o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…Notably, the application of automated DL methods to routine clinical imaging for cardiovascular risk prediction has been demonstrated from images such as retinal fundus photographs and lung cancer screening CT scans. 23,[30][31][32] However, the use of routine oncologic imaging, such as radiotherapy planning CT scans, for cardiovascular risk prediction has been less well characterized. Importantly, DL studies analyzing CAC from various cardiac CT and chest CT protocols have demonstrated success, 33 including DL models specifically measuring CAC from breast cancer radiotherapy CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the application of automated DL methods to routine clinical imaging for cardiovascular risk prediction has been demonstrated from images such as retinal fundus photographs and lung cancer screening CT scans. 23,[30][31][32] However, the use of routine oncologic imaging, such as radiotherapy planning CT scans, for cardiovascular risk prediction has been less well characterized. Importantly, DL studies analyzing CAC from various cardiac CT and chest CT protocols have demonstrated success, 33 including DL models specifically measuring CAC from breast cancer radiotherapy CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Existing machine learning methods usually rely on generalised adverse features for CAD risk prediction which may lead to low reproducibility. 68 Additionally, current machine learning approaches, 37–41 71 72 focus primarily on systemic risk factors. This does not consider the observed trends that particular locations within the coronary tree, for example, bifurcations, 10 are at significantly higher risk of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Still, cardiac CT requires unfavourable radiation exposure and some studies attempted to leverage non-cardiac imaging to investigate CAD risk factors. 37–39 Deep learning models have shown promising results in using low-dose CT imaging for lung cancer screening, 37 and risk factors such as blood pressure, smoking history and diabetes, have been successfully identified in retinal vasculature from retinal images only, 38 showing correlation with CAD risk and all-cause mortality. 39 This showcases the potential for general investigation of the anatomy of risk and patient-specific image-derived biomarkers, as these may not just be linked to cardiac CT but can also be deployed to a range of available imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple ML techniques have been proposed to automatically evaluate CAC score from dedicated cardiac and non-EKG gated chest CT scans [ 66 , 67 , 183 , 184 , 185 ]. ML techniques incorporating CAC score and other imaging parameters have been shown to be a better predictor than the traditional risk scores employed for cardiovascular disease risk stratification [ 181 , 186 , 187 , 188 , 189 ].…”
Section: Artificial Intelligence-based Long-term Mortality and Mace P...mentioning
confidence: 99%